Going from rain to gain: blue and green water management practices - Hamdy A. (Irrigation in Mediterranean agriculture: challenges and innovation for the next decades, 2008)
How to provide the growing urban centres with their water demands and combine the tremendous challenges to ensure food and environmental security? The answer to this question implies that our efforts should be directed to the management of both the blue and the green water. In many countries effective conservation and use of rainwater are seldom seen as a water resource management task. The conventional conceptualisation has neglected a large unnoticed resource: the green water source, i.e. the infiltrated rain in soil that supports all plant production, including rainfed agriculture. On the contrary, current institutional and technological responses are mostly focusing on the blue water and surface water in particular, which is indeed only a small part of precipitation. Even though countries must continue to improve management of blue water, the path of making better use of green water should be fully explored. Green water can yield positive returns in crop production beside its potential of freeing up blue water that can be used for non-agricultural economic activities as well as for maintaining required stream flows to sustain the aquatic ecosystem. To govern water from rain to gain, focus should be on more efficient use of rainwater through integrated land and water resources management, conservation farming, watershed management and rainwater harvesting.
International Conference on Irrigation in Mediterranean Agriculture: Challenges and Innovation for the Next Decades, 2008/06/17-18, Naples (Italy)